A first case of meningitis/encephalitis associated with SARS-Coronavirus-2. (May 2020) - Moriguchi, Takeshi; Harii, Norikazu; Goto, Junko; Harada, Daiki; Sugawara, Hisanori; Takamino, Junichi; Ueno, Masateru; Sakata, Hiroki; Kondo, Kengo; Myose, Natsuhiko; Nakao, Atsuhito; Takeda, Masayuki; et al.
Highlights: Novel coronavirus (SARS-Coronavirus-2:SARS-CoV-2) which emerged in Wuhan, China, has spread to multiple countries rapidly. This is the first case of meningitis associated with SARS-CoV-2 who was brought in by ambulance. The specific SARS-CoV-2 RNA was not detected in the nasopharyngeal swab but was detected in a CSF. This case warns the physicians of patients who have CNS symptoms. Abstract: Novel coronavirus (SARS-Coronavirus-2:SARS-CoV-2) which emerged in Wuhan, China, has spread to multiple countries rapidly. We report the first case of meningitis associated with SARS-CoV-2 who was brought in by ambulance due to a convulsion accompanied by unconsciousness. He had never been to any foreign countries. He felt generalized fatigue and fever (day 1). He saw doctors nearby twice (day 2 and 5) and was prescribed Laninamivir and antipyretic agents, His family visited his home and found that he was unconsciousness and lying on the floor in his vomit. He was immediately transported to this hospital by ambulance (day 9). Under emergency transport, he had transient generalized seizures that lasted about a minute. He had obvious neck stiffness. The specific SARS-CoV-2 RNA was not detected in the nasopharyngeal swab but was detected in a CSF. Anti- HSV 1 and varicella-zoster IgM antibodies were not detected in serum samples. A brain MRI showed hyperintensity along the wall of right lateral ventricle and hyperintense signal changes in the right mesial temporal lobe and hippocampus, suggesting the possibility of SARS-CoV-2 meningitis. This case warns the physicians of patients who have CNS symptoms.